Hake fish bone as a calcium source for efficient bone mineralization. (2nd April 2016) - Flammini, Lisa; Martuzzi, Francesca; Vivo, Valentina; Ghirri, Alessia; Salomi, Enrico; Bignetti, Enrico; Barocelli, Elisabetta
Abstract: Calcium is recognized as an essential nutritional factor for bone health. An adequate intake is important to achieve or maintain optimal bone mass in particular during growth and old age. The aim of the present study was to evaluate the efficiency of hake fish bone (HBF) as a calcium source for bone mineralization: in vitro on osteosarcoma SaOS-2 cells, cultured in Ca-free osteogenic medium (OM) and in vivo on young growing rats fed a low-calcium diet. Lithotame (L), a Ca supplement derived from Lithothamnium calcareum, was used as control. In vitro experiments showed that HBF supplementation provided bone mineralization similar to standard OM, whereas L supplementation showed lower activity. In vivo low-Ca HBF-added and L-added diet similarly affected bone deposition. Physico-chemical parameters concerning bone mineralization, such as femur breaking force, tibia density and calcium/phosphorus mineral content, had beneficial effects from both Ca supplementations, in the absence of any evident adverse effect. We conclude HBF derived from by-product from the fish industry is a good calcium supplier with comparable efficacy to L.